In Vitro Assessment of Dual Drug Combinations To Inhibit Growth of Neisseria gonorrhoeae - Pettus, Kevin (Antimicrob Agents Chemother, 2015)
The development of resistance to first-line antimicrobial therapies has led to recommendations for combination therapies for the treatment of gonorrhea infection. Recent studies have shown the success of combination therapies in treating patients, but few have reported on the in vitro activities of these drug combinations. An in vitro assessment of azithromycin in combination with gentamicin demonstrated inhibition of growth and suggests that clinical trials may be warranted to assess the utility of this combination in treating gonorrhea infections.